Vertigo and Dizziness Common Complaints - Brandt, Thomas; Dieterich, Marianne; Strupp, Michael (Springer London : Imprint: Springer, 2013)
Vertigo and Dizziness: Common Complaints, Second Edition revises and updates the first edition to reflect the advances that have taken place in this field.   Valid epidemiological studies are now available on the prevalence and incidence of these illnesses. There have been improvements in diagnostic criteria and important new principles in the treatment of vertigo and balance disorders are outlined for use in clinical practice, supported by video examples. Practitioners are also given access to the wealth of new, scientifically interesting findings on the pathophysiology, etiology, signs and symptoms and current treatment of peripheral and central vestibular disorders as well as somatoform vertigo, summarised in concise and accessible form.   Written by experts in the field, Vertigo and Dizziness: Common Complaints, Second Edition is a practical guide for physicians of different specializations who treat patients with vertigo including neurologists, ENT specialists, neuro-otologists, and neuro-ophthalmology and ophthalmology specialists as well as general medicine practitioners.